Insights into the Leadership Styles and Their Influence on Projects’ Success - A Case Study within the Emirate of Abu Dhabi - Al Remeithi, Abdulla Mohammed Abdulla Matar (2017)
The purposes of this dissertation were to analyze the most dominant leadership style(s) in the UAE, based on the Personality Assessment test results (15FQ+) of the Main Reference Group of 3113 Emirati Employees, and to compare it with the leadership styles of project leaders in one of the Abu Dhabi’s Government Entities, based on these project leaders’ personality assessment test results (15FQ+). It also tried to analyze the leadership styles that lead to highest project success rates within the Abu Dhabi Government Entity’s completed projects. The outcomes of this research have directly linked some leadership styles to what could make a good project leader in the Emirate of Abu Dhabi. The sample size used in this research, namely 3113 working Emiratis, which is a representative sample of the general population of working UAE nationals within the Emirate of Abu Dhabi, showed obvious patterns in the leadership styles that could be used as part of a prediction model to identify successful project managers. The patterns observed are the same for different groups like Male, Female, and different age groups like 20-30, 30-40, 40-50, and 50-60. Statistical analysis shows that the most dominant leadership styles within the UAE are the Directive and Delegative leadership styles. It was also observed from the analysis of 54 projects data and the leadership styles of the project managers that project success rates have negative correlation with the Directive leadership style in the UAE.